Large-Scale Assessment of Health-Related Physical Fitness in French Older Adults: Feasibility and Validity - Damien Mack-Inocentio; Damien Mack-Inocentio; Mehdi Menai; Eric Doré; Eric Doré; Bastien Doreau; Camille Gaillard; Camille Gaillard; Julien Finaud; Bruno Pereira; Pascale Duché; Pascale Duché (Frontiers Media S.A., 2020)
Objectives: This study aims to assess the validity, internal consistency, implementation, and feasibility of a sequence of tests, the Vitality Test Battery, designed to measure physical fitness, at a large scale in French older adults.Methods: A total of 528 volunteers (age ≥60 years) took the battery of 10 tests: 6-min walk, trunk strength, hand grip strength, medicine ball throwing, 30-s chair stand, flexibility, balance, plate tapping, ruler drop, and dual task.Results: Internal consistency was high, with the Cronbach alpha coefficients at around 0.77, explaining 64% of the variance. The test-retest correlations (0.3-0.6) between the items were acceptable and displayed an internal consistency property. Although five components explained 65% of the variance, all the items were kept because their eigenvalues were near to 0.9. External consistency was validated by a significant decrease in fitness scores (p < 0.001) with age and body mass index.Discussion: The Vitality Test Battery is a safe, valid tool for assessing physical fitness in persons aged over 60 years.